The Role of Non-Verbal Communication in Teaching English Speaking Skills: Students’ Voices - Ferginan, Yerico; Ilma, Ridha; Desvitasari, Deta (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this study was to determine the various forms of nonverbal communication employed by English teachers of a private senior high school in Palembang and their role in teaching speaking skills. This study employed a qualitative approach with observation and interview became the instruments to collect the data. The participants consisted of six eleventh-grade students who were selected based on the variation of their speaking ability: two students with high, two with medium, and two with low ability. The researchers applied thematic analysis that identified and interpreted patterns in data sets. The results showed that teachers used four primary forms of nonverbal communication: body posture (open, erect), hand gestures (active, illustrative, highlighting vital themes), eye contact (long, short), and facial expressions (smiling, joyful). This nonverbal communication played a role in increasing students' confidence, motivation, understanding, and interest in speaking English. Friendly facial expressions and illustrative hand gestures increased students' confidence, while cheerful facial expressions and hand gestures that emphasized important points enhanced learning motivation. Brief eye contact, open posture, and illustrative hand gestures helped improve comprehension. In addition, upright and relaxed posture and active hand gestures also contributed to increasing students' interest in learning. In short, English teachers needed to effectively employ nonverbal communication to provide a supportive and engaging learning environment.